Du concept psychiatrique à la métaphore théâtrale : le miroir de l’Autre dans les dramaturgies postcoloniales de Caryl Churchill et de Nick Gill - Liliane Campos (Sillages Critiques)
This article analyses the role played by psychiatry in the work of British playwrights Nick Gill and Caryl Churchill. Nick Gill’s most recent play, Mirror Teeth (2011), examines contemporary Britain’s xenophobia by reworking ethical questions and metaphors from Churchill’s early plays. His characters’ masked identities and ontological insecurity bear striking similarities to Churchill’s Hospital at the Time of the Revolution (1971) and Cloud Nine (1979). Both playwrights draw their ideas from a psycho-analytical approach to post-colonial identities, basing their assessment of their characters’ conflicting identities on a symptomatic approach to the fear of the Other. This article identifies the complexes, symptoms, and fantasies that structure identities in these three plays, and suggests that theses psychiatric motifs are far from reassuring, as they can be deprived of their healing potential. This is particularly clear in Mirror Teeth, which offers us no escape from its regressive nightmare.